Studi Kritis Ulangan 21:14-16 dan Perlakuan terhadap Perempuan Tawanan: Tinjuan Sosial Historis - Putri Wahyuni Dewanto; Inriyani Inriyani; Julita Tandiongan; Irna Bumbungan; Zhirene Zhirene (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study aims to analyze exegetically and socio-historically the text of Deuteronomy 21:10–14 concerning the treatment of female war captives in ancient Israel. This passage has often been debated as it is perceived to reflect a patriarchal system, thus requiring a comprehensive interpretation to understand its original intent. This research employs a qualitative approach based on library research, utilizing textual exegesis, historical-critical, and literary analysis of the Hebrew text, as well as an examination of the Ancient Near Eastern context. The findings reveal that the legal structure of the text is progressive and regulatory in nature, not legitimizing exploitation but rather restricting male behavior through specific procedures, including a mourning period and a process of social transition for the captive woman. The analysis of Hebrew terminology highlights symbolic meanings related to status transformation, purification, and recognition of the woman's humanity. In its socio-historical context, this law differs significantly from common practices in the Ancient Near East, which often exploited war captives, by imposing limitations on economic and social exploitation and providing a degree of protection. Theologically, the text reflects the function of the Mosaic law as a regulatory framework that introduces justice and humanity within a complex social reality. Therefore, Deuteronomy 21:10–14 is best understood as an ethical effort to limit inhumane practices rather than to endorse them.